Development of a Modified Cervical Deformity Frailty Index: A Streamlined Clinical Tool for Preoperative Risk Stratification. Issue 3 (1st February 2019) - Passias, Peter G.; Bortz, Cole A.; Segreto, Frank A.; Horn, Samantha R.; Lafage, Renaud; Lafage, Virginie; Smith, Justin S.; Line, Breton; Kim, Han Jo; Eastlack, Robert; Hamilton, David Kojo; Protopsaltis, Themistocles; et al.
Abstract : Study Design: Retrospective review. Objective: Develop a simplified frailty index for cervical deformity (CD) patients. Summary of Background Data: To improve preoperative risk stratification for surgical CD patients, a CD frailty index (CD-FI) incorporating 40 health deficits was developed. While novel, the CD-FI is clinically impractical due to the large number of factors needed for its calculation. To increase clinical utility, a simpler, modified CD-FI (mCD-FI) is necessary. Methods: CD patients (C2-C7 Cobb>10°, CL>10°, cSVA>4 cm, or CBVA>25°) >18 year with preoperative CD-FI component factors. Pearson bivariate correlation assessed relationships between component deficits of the CD-FI and overall CD-FI score. Top deficits contributing to CD-FI score were included in multiple stepwise regression models. Deficits from model with largest R 2 were dichotomized, and the mean score of all deficits calculated, resulting in mCD-FI score from 0 to 1. Patients were stratified by mCD-FI: Not Frail (NF, <0.3), Frail (0.3–0.5), Severely Frail (SF, >0.5). Means comparison tests established correlations between frailty category and clinical outcomes. Results: Included: 121 CD patients (61 ± 11 yr, 60%F). Multiple stepwise regression models identified 15 deficits as responsible for 86% of the variation in CD-FI; these factors were used to construct the mCD-FI. Overall, mean mCD-FI was 0.31 ± 0.14. Breakdown of patients by mCD-FI category: NF: 47.9%, Frail: 46.3%, SF: 5.8%. Compared with NF and Frail, SF patients had the longest inpatient hospital stays ( P  = 0.042), as well as greater baseline neck pain ( P  = 0.033), inferior Neck Disability Index scores ( P <0.001) and inferior EQ-5D scores ( P  < 0.001). Frail patients had higher odds of superficial infection (OR:1.1[1.0–1.2]), and SF patients had increased odds of mortality (OR:8.3[1.3–53.9]). Conclusion: Increased frailty, assessed by mCD-FI, correlated with increased length of stay, neck pain, and decreased health-related quality of life. Frail patients were at greater risk for infection, and severely frail patients had greater odds of mortality. This relationship between frailty and clinical outcomes suggests that mCD-FI offers clinical utility as a preoperative risk stratification tool. Level of Evidence: 3 Abstract : This study develops and assesses the clinical applicability of a modified frailty index for surgical cervical deformity patients. Increasing frailty correlated with increased complication incidence, longer length of stay, and inferior health-related quality of life. These associations suggest the mCD-FI may serve as a valuable preoperative risk stratification tool.